THE USE OF INTERACTIVE TECHNIQUES IN THE FORMATION OF PRACTICAL SKILLS IN NATURAL SCIENCE LESSONS - Mirzabekova Gumshagul Xojabekovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article explores the effectiveness of interactive techniques in enhancing the practical skills of students in natural science lessons. It emphasizes the role of active learning strategies in fostering student engagement, critical thinking, and the application of scientific concepts. Through a comprehensive literature review and the presentation of empirical findings, this study aims to provide educators with insights into the integration of interactive methods in their teaching practices.